Quranic Analysis: A Critical Examination of Gender in Islamic and Western Paradigms - Furhan Zubairi; Jamal Ahmed Bashier Badi; Mohammad Eisa Ruhullah (MAQOLAT: Journal of Islamic Studies, 2024)
The modern era epitomizes a period of profound transformation across diverse spheres including science, technology, politics, and warfare, characterized by discovery, innovation, and globalization. European powers and their colonies spearheaded a comprehensive colonization endeavor encompassing politics, economics, and culture, shaping what we recognize today as the modern world. This era heralded the ascendance of capitalism, liberalism, materialism, and globalization, predominantly led by Western hegemony, notably post-Cold War American capital, extending its influence globally. Modernity, with its core tenets of moral autonomy, human rights, civil equality, consumerism, market freedom, and secularism, presents a formidable challenge to traditional religious frameworks, particularly within the Abrahamic Faiths. The secularization of society, relegating religion to the private sphere, prompts shifts within religious communities, including Islam, regarding values, ethics, and gender roles. Muslims navigate a complex landscape, torn between adherence to Islamic principles and the pervasive secular worldview propagated by the modern West. Despite maintaining Islamic beliefs and practices, individuals are inevitably influenced by the dominant secular paradigm, shaped by Western education systems and cultural norms. This convergence engenders a tension wherein Islamic principles are often interpreted through a liberal and secular lens, leading to internal conflicts, doubts, and confusion. This article endeavors to establish a framework for understanding gender within Islam, rooted in the foundational texts of the Quran and Sunnah. While acknowledging the potential contributions of sociology, anthropology, and gender studies to the discourse, the focus remains on traditional Islamic scholarship, drawing insights from Islamic jurisprudence and theology to elucidate gender roles and relations. By grounding the discussion in Islamic principles, the aim is to reconcile contemporary understandings of gender with the enduring teachings of Islam, offering clarity amidst the complexities of modernity. The research methodology for this article is primarily rooted in Islamic Hermeneutics or Islamic Textual Analysis that involves a systematic examination and understanding of scripture to derive meaning and guidance. The complexity of the topic also demands a nuanced exploration of the intersections between religion, culture, and modernity, with a specific focus on the evolving understanding of gender within the Muslim community. The research explored two questions: How does scripture define, discuss, and describe gender, and what implications does the Islamic paradigm of gender hold for contemporary societal attitudes and practices? As a result, the text highlights how society, media, literature, and culture heavily influence how we perceive ideas and process information, including our understanding and application of Islam. This can lead to conflict within ourselves, especially when we interpret Islamic texts and guidance through the prism of modern liberal thought or other ideologies. As Muslims, we need to remain grounded in our teachings and understanding that are rooted in the words of God and the example of His Prophet ﷺ. Our morals, values, ethics, and principles should not be shaped by the changing standards of society around us.